Kinetic Aspects of the Interaction of Blood Clotting Enzymes - Hemker, H. C; Veltkamp, J. J; Loeliger, E. A (Thrombosis and Haemostasis, 1968)
Application of enzyme kinetics to the results of thrombotest estimations in correlation with specific clotting factor estimations has led to the recognition of a protein moiety that occurs in plasma in vitamin K deficiency and acts as a competitive inhibitor of thrombin formation. A hypothesis is given by which the occurrence of this inhibitor is explained in terms of a biphasic synthesis of the vitamin K-dependent clotting factors.